2020
DOI: 10.1021/acs.jpca.9b11122
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Reactions in Ionized Ammonia Clusters: A Direct Ab Initio Molecular Dynamics Study

Abstract: Ammonia cluster cations are a chemical species that has recently attracted considerable research attention as an ion−molecule reaction species in the planetary atmosphere, surface reaction species in materials chemistry, and super-alkali species. Reactions of the radical cation of an ammonia cluster, [(NH 3 ) n ] + (n = 2−6), following the ionization of the parent neutral cluster, were investigated using direct ab initio molecular dynamics to elucidate the reactions of the ammonia cluster cation under astroche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…A similar tendency is obtained at the PBE0-D3/6-311++g­(2df,2pd), B3LYP-D3/6-311++g­(2df,2pd), MP2/aug-cc-pvdz, MP2/aug-cc-pvtz, and MP2/6-31++g­(d,p) levels, as shown in Table S1 in the Supporting Information. These geometric structure parameters of MP2 with basis set investigations are in good agreement with DFT. , The trend is consistent with the previous view that bond lengths decrease gradually with the increase of the number of n . , Moreover, we present the average O–H bond lengths as well as the average ∠H···NH bond angles in Figure . As the n value increases, the N–H bond lengths and ∠H···NH bond angles increase, leading to a decrease of N···H bond lengths.…”
Section: Resultssupporting
confidence: 90%
“…A similar tendency is obtained at the PBE0-D3/6-311++g­(2df,2pd), B3LYP-D3/6-311++g­(2df,2pd), MP2/aug-cc-pvdz, MP2/aug-cc-pvtz, and MP2/6-31++g­(d,p) levels, as shown in Table S1 in the Supporting Information. These geometric structure parameters of MP2 with basis set investigations are in good agreement with DFT. , The trend is consistent with the previous view that bond lengths decrease gradually with the increase of the number of n . , Moreover, we present the average O–H bond lengths as well as the average ∠H···NH bond angles in Figure . As the n value increases, the N–H bond lengths and ∠H···NH bond angles increase, leading to a decrease of N···H bond lengths.…”
Section: Resultssupporting
confidence: 90%
“…On the other hand, in the case of or the [PhOH-(NH3)2-6] + cluster cations, proton transfer is spontaneous even in the presence of two ammonia molecules. 28 Further, the BOMD trajectories were also calculated for several PhOH-(NH3)5-10 clusters (starting from 5A, 5C, 6A, 6B, 6E, 7A, 7B, 7C, 8A, 8B, 8C, 9B, 10C, 10E, and 10F geometries, from Ref. 16).…”
Section: (B) Proton Transfer In Bomd Simulationsmentioning
confidence: 99%
“…In the present study, the intracluster reactions of O­(X)­(H 2 O) n (X = 3 P, 1 D, and 1 S, and n = 1–6), following the photoelectron detachment of a water cluster of an oxygen radical anion (O – (H 2 O) n , n = 1–6), were investigated using the direct ab initio molecular dynamics (AIMD) method. Three low-lying electronic states of oxygen atoms, O­( 3 P), O­( 1 D), and O­( 1 S), were examined. We found that the O­( 1 S)­(H 2 O) n complexes spontaneously convert into H 2 O 2 after electron detachment.…”
Section: Introductionmentioning
confidence: 99%